Dialogue Translation Shift Analysis in Karyamin’s Smile by Ahmad Tohari - Saputra, Kirana Septiani Wanodya; Darta, Deta Maria Sri (Universitas Negeri Semarang, 2020)
A dialogue carries feelings and thoughts of a character in a story. It might also convey emotional expressions. In the translating process, emotional expression, one of many factors which needs to be considered, is regarded as expressive meaning. Thus, in translating dialogues, it is necessary to preserve the emotional expression of the source language. As translation process involves two different languages, there could be changes occurred from ST to TT. Therefore, this study aims to use translation shift to seek the changes in dialogue translation in some short stories in Karyamin’s Smile. This research is a qualitative-descriptive analysis as it proposes to identify the types of shift used in dialogue translation and analyze the equivalence to the ST. The dialogues that have been categorized were examined the equivalence using a translation assessment rubric proposed by Khanmohammad and Osanloo (2009). The result shows that each type of shift used more or less affects the equivalence of dialogue translation. The types of shift that are mostly appeared are structure shift and unit shift. Those types produce some patterns. The patterns found in structure shift are passive to active forms, affirmative to interrogative sentence, affirmative to imperative sentence. In unit shift, the patterns found are word to phrase, phrase to sentence, and word to sentence. In sum, structure shift can create more significant changes compared to unit shift as the patterns found mostly result in the changing intention of dialogues.